A systematic review and meta-analysis of individual differences in naturalistic sleep quality and episodic memory performance in young and older adults. (August 2021) - Hokett, Emily; Arunmozhi, Aditi; Campbell, Jessica; Verhaeghen, Paul; Duarte, Audrey
Highlights: Sleep-memory associations similar for PSG and actigraphy. Slow wave sleep positively associated with memory, particularly for young. Wake after sleep onset negatively associated with memory, particularly for old. Abstract: Better sleep quality has been associated with better episodic memory performance in young adults. However, the strength of sleep-memory associations in aging has not been well characterized. It is also unknown whether factors such as sleep measurement method (e.g., polysomnography, actigraphy, self-report), sleep parameters (e.g., slow wave sleep, sleep duration), or memory task characteristics (e.g., verbal, pictorial) impact the strength of sleep-memory associations. Here, we assessed if the aforementioned factors modulate sleep-memory relationships. Across age groups, sleep-memory associations were similar for sleep measurement methods, however, associations were stronger for PSG than self-report. Age group moderated sleep-memory associations for certain sleep parameters. Specifically, young adults demonstrated stronger positive sleep-memory associations for slow wave sleep than the old, while older adults demonstrated stronger negative associations between greater wake after sleep onset and poorer memory performance than the young. Collectively, these data show that young and older adults maintain similar strength in sleep-memory relationships, but age impacts the specific sleep correlates that contribute to these relationships.